Pengembangan Sistem Informasi Akuntansi berbasis Web (Studi Kasus: Language Center Kediri) - Tasya Permatasari; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Accounting Information System is a system that collects, stores and processes financial data within a company. In the income cycle of one company, if it has an effective accounting information system, the system will make a good effect on the success of the company from a financial and general perspective in the long term. LC Language Center or commonly known as Kampung English LC is a company engaged in the service sector which in its vanue has utilized information systems or websites to facilitate and accelerate business processes. Reviewing some of the problems obtained related to information systems within the company, especially accounting information systems that are not yet adequate and meet the needs, a web-based accounting information system is developed which is expected to meet the needs, support and facilitate decision makers within the company in collecting, storing and processing more integrated financial data. The seven main features of this system are Dashboard, Estimated Account, Transaction Journal, Bank Reconciliation, General Ledger, Profit and Loss and Balance Sheet. The development of a web-based system developed with SDLC Rapid Application Development will be implemented with the Laravel framework using the PHP programming language and Javascript. The tests carried out on the functional requirements of the system are in the form of unit testing with the white box method and validation testing with the black box method where this functional test gets 100% valid results. While the non-functional test, namely usability, was tested using the SUS method which resulted in a score of 73.